Achieving sustainable practice: Working patterns of professional musicians. - Bennett, Dawn (International Society for Music Education, 2004)
In an endeavour to address issues pertaining to education of the professional musician, identifying factors that characterise the longitudinal career patterns of professional musicians is both judicious and important. The purpose of this research was to identify the performance and non-performance roles undertaken by musicians; the proportion of time spent on average in each role, and the skills utilised in facilitation of those roles. The Australian-based study included one hundred and sixty-five artists and musicians who reflected upon their careers and their education, and results revealed that less than 50% of a professional musician's working time is spent in performance. In light of these results, the research attempts to understand what music and other attributes are required by a musician in order to achieve sustainable professional practice.